Slavic activists and socio-political situation in Bosnia at the turn of the 19th century. The Foundations of the contemporary ethnic divisions - Paszkiewicz, Jędrzej (Balcanica Posnaniensia. Acta et studia, 2020)
The aim of the article is to show the forms and content of public and political activity of the Slavic elites in Bosnia and Herzegovina during the time of Habsburg rule (1878–1914). The research into the press releases and academic publications allows to show the most prominent circles and individuals who aspired to be the representatives of the people, defined in accordance with ethnic and religious divisions. These groups are characterised via an analysis of the correlation between the socio-political circumstances in Bosnia and the external influences (such as ideologies, personal and organisation relations, the impact of the state authorities). The political stances among the most prominent circles are portrayed in the context of the legal and institutional solutions regarding Bosnia, as well as the ethnic and religious policy of the Habsburg administration.